Replacing the Draize eye test: Impedance spectroscopy as a 3R method to discriminate between all GHS categories for eye irritation. Issue 1 (December 2018) - Lotz, C.; Kiesewetter, L.; Schmid, F.; Hansmann, J.; Walles, H.; Groeber-Becker, F.
Abstract Highly invasive animal based test procedures for risk assessment such as the Draize eye test are under increasing criticism due to poor transferability for the human organism and animal-welfare concerns. However, besides all efforts, the Draize eye test is still not completely replaced by alternative animal-free methods. To develop anin vitro test to identify all categories of eye irritation, we combined organotypic cornea models based on primary human cells with an electrical readout system that measures the impedance of the test models. First, we showed that employing a primary human cornea epithelial cell based model is advantageous in native marker expression to the primary human epidermal keratinocytes derived models. Secondly, by employing a non-destructive measuring system based on impedance spectroscopy, we could increase the sensitivity of the test system. Thereby, all globally harmonized systems categories of eye irritation could be identified by repeated measurements over a period of 7 days. Based on a novel prediction model we achieved an accuracy of 78% with a reproducibility of 88.9% to determine all three categories of eye irritation in one single test. This could pave the way according to the 3R principle to replace the Draize eye test.